Mathematically Gifted Students’ Experience With Their Teachers’ Mathematical Competence and Boredom in School: A Qualitative Interview Study - Smedsrud, Jørgen Hammer; Nordahl-Hansen, Anders; Idsøe, Ella (Frontiers in Psychology, 2022)
Competent mathematical teachers who have knowledge about gifted students’ needs can challenge them in math and prevent boredom and possible underachievement. This retrospective study explores how Norwegian gifted students perceive their earlier teachers’ mathematical competency, as well as their reflection about boredom in school. The data were collected through qualitative semistructured interviews with 11 mathematically gifted students. The informants ranged in age from 16 to 19 years and were asked about how they experienced their math classes, teachers and social aspects. The results indicate that students describe their teachers as having less mathematical knowledge in earlier school than later years.